Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

‘Learning the rules of the game‘: Emotional labor and the gendered academic subject in the United States - Bartos, Ann E.; Ives, Sarah (Gender, Place & Culture, 2019)
In this article, we investigate how entrenched sexism in higher education can take root in graduate school, where many of us learn the ‘rules of the academic game’ through our roles as teaching assistants (TAs). Feminist and antiracist scholars have documented how these ‘rules of the game’ are scripted on different academic bodies. We focus this article on the stubborn persistence of sexism in university life through the everyday, mundane forms of emotional labor and care that TAs feel obligated to perform. As the current #MeToo movement reminds us, sexism, sexist exploitation, and oppression are as evident today as they were decades ago when feminist scholars and activists challenged the masculinism of geographical discourse through examinations of power, knowledge, and subjectivity. Our research returns to these themes by examining TAs’ experiences of sexism in the classroom through the lens of critical care ethics. A focus on TAs brings attention to the constitution of the gendered academic subject and identifies the emotional labor required to manage this subject. We believe that the durability of sexism warrants an investigation of the sites where women learn their ‘place’ in the academy.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; care; charge émotionnelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; stratégie féministe; systèmes d'oppressions; thématiques; travail; universitaires; éducation; états-unis

Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (ENS Éditions, 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Section: 257 pages : tableaux ; 23 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)
https://www.jstor.org/stable/10.5406/jazzculture.2.2019.0059
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; care; discipline; discours dominant; femmes* artistes; genre; histoire; histoire et politique; identités LGBTQIA2+; maternité; montréal; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; éthique

Affamée: une histoire de mon corps - Gay, Roxane (Édito, 2019)
« À douze ans, Roxane Gay est victime d'un viol collectif orchestré par celui qu'elle croit être son petit ami. Elle y perd son enfance et son innocence, et grandit en taisant ce drame à son entourage. Pour survivre, elle se met à manger, tout le temps. Elle fait de la nourriture son refuge, et de la graisse, une forteresse qu'elle érige pour se protéger du désir des hommes. Elle devient obèse. Dans cet ouvrage introspectif, elle nous raconte l'histoire de son corps, de sa faim, de sa détresse, de sa volonté de disparaître, intimement et paradoxalement liée à son furieux désir d'être vue, comprise et aimée. Elle y décrit l'incessant combat qu'elle doit mener, l'un des plus douloureux qui soit, tant physiquement que psychologiquement. Parce qu'être obèse est socialement inacceptable. Par son témoignage résolument touchant, Roxane Gay partage avec nous une leçon de vie fondamentale : nous devrions tous faire preuve de bienveillance envers la réalité du corps des autres et nous réconcilier avec le nôtre. »–Quatrième de couverture.
Section: 305 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; care; corps; cours; discipline; discours dominant; grossophobie; lit4700; littérature; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; violences; études littéraires

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Theorizing Family Change: A Review and Reconceptualization - Knapp, Stan J.; Wurm, Greg (Journal of Family Theory & Review, 2019)
We review how recent family scholarship theorizes recent family change as either a process of deinstitutionalization, in which family can no longer be understood in institutional terms, or a process of diversification, in which family life is expanding but not losing its institutional character. We argue that both approaches emerge out of and depend on a social institutional framework for understanding family that was developed in 20th-century sociology. Despite producing a wealth of research, both approaches have difficulty adequately conceptualizing the institutional character of family and providing ways of theorizing family change. We introduce an alternative to a social institutional framework, a Weberian institutional logics approach, which provides a different way to understand the institutional character of family life and thereby affords new interpretations and avenues for theory and research on family change in the 21st century.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; famille; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Travailler la terre et déconstruire l’hétérosexisme: expérimentations écoféministes - Rimlinger, Constance (Travail, genre et sociétés, 2019)
À partir de l’ethnographie de trois lieux ruraux (deux fermes et un gîte) tenus par des femmes lesbiennes et/ou queer qui s’inscrivent dans une critique écologiste et anticapitaliste de la société tout en questionnant les normes de genre et de sexualité, nous interrogerons la signification de ces choix de vie alternatifs au regard de l’identité des actrices et de la manière dont ils enrichissent la compréhension de la constellation des mouvements écoféministes. Nous observerons qu’avec le déplacement de la ville vers la campagne, et du monde salarié vers l’agriculture de subsistance, elles doivent mettre en place de nouvelles stratégies pour lutter contre l’isolement et s’intégrer localement. Simultanément, ce retour à la terre leur offre de nouvelles possibilités d’émancipation, d’engagement et de soutien aux femmes et aux minorités. Le travail agricole, l’engagement féministe et la politisation du quotidien constituent les différentes facettes d’un même projet : celui de chercher une voie plus juste et plus durable pour notre société.
Keywords: 2000 à aujourd'hui; 2010-2019; agriculture; approches et analyses; care; com5170; cours; discipline; environnement; europe; france; hétérosexisme; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; séparatisme lesbien; thématiques; travail; vie rurale; écoféminisme; écologie queer

Les amitiés radicales - Toffoli, Camille (Liberté, 2019)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; hétérosexisme; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; systèmes d'oppressions; thématiques; travail social; trs1205; états-unis